2008
DOI: 10.1513/pats.200709-150mg
|View full text |Cite
|
Sign up to set email alerts
|

Positive Pressure Therapy: A Perspective on Evidence-based Outcomes and Methods of Application

Abstract: The sleep medicine community has increasingly recognized the necessity that clinical care be based on high-quality levels of evidence. Although research supports a favorable influence of positive airway pressure (PAP) therapy on risk for significant adverse outcomes in patients with severe obstructive sleep apnea-hypopnea (OSAH), welldesigned trials are still required to elucidate the effect of PAP on health, quality of life, and economic risks in patients with milder OSAH. Similarly, although there is strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 113 publications
1
24
0
7
Order By: Relevance
“…In keeping with other transverse and longitudinal studies [6,7], very recent new data from the Sleep Heart Health study [8] confirm an increased adjusted incidence of stroke in a wide community-based sample of males with AHI .19 events?h -1 (HR: 2.86) and female with AHI .25 events?h -1 . Furthermore, SAHLIN et al [10] have reported a higher risk of long-term mortality in stroke patients with OSA (AHI .15 events?h -1 ; HR 1.76), with similar results to those of our group (AHI .20 events?h -1 ; HR 2.91) [11].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In keeping with other transverse and longitudinal studies [6,7], very recent new data from the Sleep Heart Health study [8] confirm an increased adjusted incidence of stroke in a wide community-based sample of males with AHI .19 events?h -1 (HR: 2.86) and female with AHI .25 events?h -1 . Furthermore, SAHLIN et al [10] have reported a higher risk of long-term mortality in stroke patients with OSA (AHI .15 events?h -1 ; HR 1.76), with similar results to those of our group (AHI .20 events?h -1 ; HR 2.91) [11].…”
Section: Discussionsupporting
confidence: 77%
“…Nasal continuous positive airway pressure (CPAP) is the most recognised and most cost-effective treatment for severe or symptomatic OSA [6]. Large-scale studies have established moderate-to-severe untreated OSA as an independent modifiable risk factor for stroke and other cardiovascular events (CVE) [7][8][9].…”
Section: #1mentioning
confidence: 99%
“…In several studies, normalization of sleep architecture, reduction of daytime sleepiness, improvement in mood and quality of life, reduction of motor vehicle crashes and a decrease in cardiovascular events have been demonstrated [1,2]. In addition, there are sufficient data to conclude that in severe OSAS, PAP therapy is associated with improved survival [3]. These positive treatment effects depend substantially on the adherence of the patient to the therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) is considered the ''standard of care'' for the treatment of OSA. Therapeutic use of CPAP mitigates many of the acute pathophysiologic responses that result from sleep-disordered breathing [13,14]. Yet, despite these benefits, therapeutic acceptance and adherence remain significant challenges to patients and clinicians.…”
Section: Introductionmentioning
confidence: 99%